Decentering fashion on the Silk Roads : craft and responsible fashion dynamics in Central Asia - Mallon, Stefanie; Mihaleva, Galina (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Decentering Fashion on the Silk Roads focuses on the dynamism of fashion, textile craft, heritage and sustainability in Central Asia and beyond. The compelling series of accounts provides a comprehensive set of insights and impressions collected from both fashion academics, designers and practitioners from around the globe who journeyed through Uzbekistan and Kazakhstan and from those who live and work in this region. It showcases ways in which local textile craft practices can inform the modern fashion industry into becoming more sustainable. The book opens by exploring the importance of the old 'Silk Roads' crossing through the heart of the world in Central Asia, serving not only as trade routes but also allowing knowledge, art and practices to be transmitted between the Orient and the Occident - enabling ideas to flourish and cultural dispositions to develop from Antiquity until Modernity. The unique set of chapters that follow examine and highlight the growing opportunities and lessons this region has to offer to Western fashion through local artistry and craft, and points toward the urgent need to slow down and adopt responsible principles and practices. The book constitutes a warm appreciation of the experiences and grateful thanks to the many communities from all different background and ages who contributed. This rich travelogue is a refreshing resource for international scholars and postgraduate students studying and researching fashion theory and management in particular. It will also be of interest to anthropologists, cultural studies and textiles scholars"--
Keywords: Clothing trade -- Environmental aspects -- Asia, Central; Sustainable development -- Asia, Central; BUSINESS & ECONOMICS / Industries / Textile Industry; SOCIAL SCIENCE / Anthropology / Cultural; CRAFTS & HOBBIES / Fashion